Učenje naravoslovja za slepe in slabovidne učence - Plazar, Janja (Revija za elementarno izobraževanje, 2015)
Teaching Science to Blind or Partially Sighted Students. Science education is of equally great importance to blind or partially sighted children as it is to fully-sighted children. Nowadays, science education is based predominantly on the principle of constructivism, in which children are engaged as active participants. Such learning processes enable them to acquire scientific knowledge and develop the ability to think and solve problems in a logical manner. This paper illustrates how science education methods and tools need to be adapted for blind or partially sighted students, in order for them to become active members of the learning process, taking into account that they perceive the world differently than fully-sighted children.
Keywords: science education; blind or partially sighted students; inquiry-based learning; adjusted educational tools; inclusion